Evasion of cytotoxic T lymphocyte (CTL) responses by nef-dependent induction of Fas ligand (CD95L) expression on simian immunodeficiency virus-infected cells. - Xu, X; Screaton, G; Gotch, F; Dong, T; Tan, R; Almond, N; Walker, B; Stebbings, R; Kent, K; Nagata, S; Stott, J; Mcmichael, A (1997)
Inoculation of macaques with live attenuated SIV strains has been shown to protect against subsequent challenge with wild-type SIV. The protective mechanism(s) remain obscure. To study the effect in more detail, we have investigated the role of virus-specific CTL responses in macaques infected with an attenuated SIV strain (pC8), which has a four-amino acid deletion in the nef gene, as compared with the wild-type SIVmac32H clone (pJ5). Cynomolgus macaques infected with pC8 were protected against subsequent challenge with pJ5 and did not develop any AIDS-like symptoms in the 12 months after infection. The pC8-induced protection was associated with high levels of virus-specific CTL responses to a variety of viral antigens. In contrast, pJ5-infected macaques had little, if any, detectable CTL response to the viral proteins after three months. The latter group of macaques also showed increased Fas expression and apoptotic cell death in both the CD4(+) and CD8(+) populations. In vitro, pJ5 but not pC8 leads to an increase in FasL expression on infected cells. Thus the expression of FasL may protect infected cells from CTL attack, killing viral-specific CTLs in the process, and providing a route for escaping the immune response, leading to the increased pathogenicity of pJ5. pC8, on the other hand does not induce FasL expression, allowing the development of a protective CTL response. Furthermore, interruption of the Fas-FasL interaction allows the regeneration of viral-specific CTL responses in pJ5-infected animals. This observation suggests an additional therapeutic approach to the treatment of AIDS.